Gender, age, and socioeconomic status roles in elementary school academic: A systematic literature review - Delora Jantung Amelia; Bahrul Ulum; Abdurrohman Muzakki (Universitas Muhammadiyah Malang, 2025)
Academic performance in elementary school is influenced by various factors such as gender, age, and socioeconomic status. However, how these variables interact and impact learning outcomes remains inconclusive. This study aimed to (1) summarize trends and the role of gender, age, and socioeconomic status in academic ability reported in Scopus-indexed journals, and (2) describe their specific influence at the elementary school level. The literature search was conducted using thirteen articles published between 2017 and 2024 met the eligibility criteria. This study employed a Systematic Literature Review (SLR) using the PRISMA framework, encompassing four stages: identification, screening, eligibility, and inclusion. Article selection was based on relevance, research design, and publication date. Descriptive and comparative analyses were applied to examine study trends, country contributions, and findings. Results revealed that most studies used quantitative approaches, with Spain contributing the highest number of publications. The findings indicated that gender differences had a minimal impact on academic achievement, while age and socioeconomic status showed a more significant influence. These results highlight the need for educational policies that focus on reducing economic disparities and addressing age-related academic needs. This review serves as a useful reference for future researchers exploring factors that influence academic performance in primary education.